Online Dating Application User Relationship Development in Finding a Life Partner (Phenomenological Study of Women Using Online Dating Applications in Jakarta) - Marghaputra, Putu Arindya Laksmidewi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The development of digital technology has changed the way people communicate. With the advancement of technology, online dating is becoming a thing. three women who use a date app were interviewed for these qualitative studies. By revealing oneself through a date app, the researchers hope to gain a better knowledge of the process of relationship growth experienced by the participants. Self-disclosure theory, social penetration theory, and computer-mediated communication were used as references in this study (CMC). This study uses the phenomenological method to explore individual knowledge in the construction of meanings and concepts connected to the process of developing relationships with targeted partners through computer-mediated communications (CMC). The findings show that on line dating app users reveal themselves to possible partners, with the depth of self-disclosure increasing in tandem with relationship intimacy.